2020
DOI: 10.1007/s00787-020-01644-y
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal maternal infections and children’s socioemotional development: findings from the UK Millennium Cohort Study

Abstract: Previous research suggests that prenatal maternal infections may be associated with increased odds of children having a neurodevelopmental disorder. However, little evidence exists on associations with broader child outcomes, especially subclinical symptoms. Participants were the N = 14,021 members of the population-representative UK Millennium Cohort Study. We examined associations between prenatal maternal infections, both maternal-reported and hospital-recorded, and children’s socioemotional development, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…These results support those of previous studies of acetaminophen use in pregnancy and child neurodevelopmental and behavioral outcomes, which reported the confounding effect of prenatal alcohol consumption [ 3 6 ]. Furthermore, previous studies have found an association between maternal infection and child development including an increased risk for autism spectrum disorders [ 42 , 43 ], social and communication problems [ 44 ], and emotional symptoms [ 45 ]. However findings have been inconsistent and some studies have not found an association, which may be due to differences in the covariates included in the models, the severity of infection [ 46 ], and differences in trimester of infection [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results support those of previous studies of acetaminophen use in pregnancy and child neurodevelopmental and behavioral outcomes, which reported the confounding effect of prenatal alcohol consumption [ 3 6 ]. Furthermore, previous studies have found an association between maternal infection and child development including an increased risk for autism spectrum disorders [ 42 , 43 ], social and communication problems [ 44 ], and emotional symptoms [ 45 ]. However findings have been inconsistent and some studies have not found an association, which may be due to differences in the covariates included in the models, the severity of infection [ 46 ], and differences in trimester of infection [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a cohort study using data from Boston and Providence, USA, found prenatal bacterial infections to be associated with reduced cognitive performance at age 7 (Lee et al ., 2020). However, other research, conducted by Hall et al . (2021) using data from a UK cohort study, found no association between hospital-recorded prenatal infections and childhood socioemotional developmental outcomes at age 3, but did find self-reported maternal infections to be associated with increased emotional problems.…”
Section: Introductionmentioning
confidence: 87%
“…Maternal prenatal bacterial infections have been linked with lower mean IQ scores at age 7 [ 4 ], and viral infections have shown associations with decreased IQ scores at age 7 with strong effect sizes [ 5 ] and learning disabilities [ 6 ]. In addition to reported effects on children’s cognition [ 7 ] and socioemotional difficulties [ 8 ], maternal infections have also been linked to a variety of psychiatric conditions such as bipolar disorder and schizophrenia [ 9 , 10 ]. These studies demonstrate associations between maternal infections and general difficulties in cognition, behavior, and psychopathology.…”
Section: Introductionmentioning
confidence: 99%